Pengaruh Sistem Informasi Pengelolaan Keuangan Daerah Terhadap Kualitas Laporan Keuangan - Maulana Yusup (Jurnal Ekonomi, Bisnis dan Entrepreneurship, 2016)
The purpose of this study to determine the influence of regional financial information system on the quality of financial statements. The object of research is the application of Financial Management System (SIPKD). This study uses qualitative descriptive method using saturated sampling. Based on the calculation, the coefficient of determination (R Square) of 0.721. This indicates that the application of regional financial information system (X) affects the quality of the regional financial report (Y) amounted to 72.1%, while the remaining 27.9% is influenced by other factors which may affect the quality of financial reporting area. The results showed that there is significant regional financial information system on the quality of the regional financial report.